Geochronology and Petrogenesis of Early Pleistocene Dikes in the Changbai Mountain Volcanic Field (NE China) Based on Geochemistry and Sr-Nd-Pb-Hf Isotopic Compositions - Li, Meng-Meng; Xu, Zhi-Tao; Ventura, Guido; Pan, Xiao-Dong; Han, Di; Gu, Guo-Hui; Yan, Dong-Han; Pan, Bo; Feng, Jing-Qiao (Frontiers in Earth Science, 2021)
Changbai Mountains intraplate volcanism (NE China) developed above the 500 km deep stagnant portion of the Pacific slab in the last 20 Ma. The more recent activity includes a shield forming stage (2.8-0.3 Ma), the Tianchi cone construction stage (1.5-0.01 Ma), and a caldera-forming stage (0.2 Ma-present). The petrogenesis of the volcanic products between the first two stages and the possible role of of geodynamics and local tectonics in controlling the volcanism are lacking of specific studies. Here, we present structural and whole-rock geochemical and zircon Hf isotopic data on Pleistocene dikes of the Changbai Mountains at the transition from the shield-forming to the Tianchi stage with the aim to constrain their age and the source(s) of the magma. The dikes represent the shallower feeding system of monogenetic cones and have a NW-SE strike, which is also the preferred strike of the major fault affecting the area and along which the Changbai Mountains monogenetic scoria cones align. The dikes have a potassic affinity and a trachybasaltic composition. Their zircon U–Pb age is 1.19 -1.20 Ma (Calabrian). The trachybasalts are enriched in Rb, Ba, Th, U, Nb, Ta, K, Pb and LREE, and slightly depleted in Sr, Zr, Hf, Ti and HREE with a weak negative Eu/Eu* (δEu = 0.96–0.97). The trace elements and isotopic compositions are compatible with an OIB-type source with an EMI signature. The calculated (87Sr/86Sr)i = 0.705165–0.705324), (143Nd/144Nd)i= 0.512552–0.512607), the relatively low εNd(t)=-0.58 to -1.65, and Hf model ages (TDM2) of 1768–1562 Ma suggest that the trachybasaltic dikes underwent crustal contamination by a Mesoproterozoic, relatively basic lower crust. The source of the Calabrian trachybasalts consists of asthenospheric melts modified by a sub-continental lithospheric mantle. These melts upwell from depth and stop at the crust-mantle interface where underplating processes favor the assimilation of ancient lower crust material. During the ascent to the surface along deep-seated crustal discontinuities, these magmas weakly differentiate.